The Impact of President Election, Celebrity Endorsement, and Product Variation to Brand Image and Purchase Intention on Sang Pisang Business - Lidia Agustin; Jony Oktavian Haryanto; Liza Agustina Maureen Nelloh (International Journal of Business Studies, 2021)
The situation of the 2019 presidential election was enough to take the attention of many parties in Indonesia because there were several conflicts. With the situation of the last presidential election, the researchers wants to examine the impact of it to the business of Sang Pisang that owned by Kaesang Pangarep who is the son of the Presidential Candidates in the 2019 presidential election, and also examine does Kaesang Pangarep's popularity as a celebrity or influencers, the variety of products and brand image have influenced the Sang Pisang Business. The findings of this study indicate that there is a direct effect of President Election, Celebrity Endorsement, Product Variation, and Brand Image towards Purchase Intention, there is direct effect of the Celebrity Endorsement towards Brand Image and also there is indirect effect of Celebrity Endorsement towards Purchase Intention mediated by Brand Image of Sang Pisang in Jabodetabek, and all of the effect is significant.